Implementasi Aplikasi Quizizz dalam Evaluasi Pembelajaran Fiqih di MAN 3 Kebumen - Azhar, Saefudin; Subarkah, Imam (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Implementation of the Quizizz Application in the Evaluation of Fiqih Learning at MAN 3 Kebumen.The purpose of this study was designed to: (1) To find out the implementation of the Quizziz Application used in the evaluation of Fiqih learning at MAN 3 Kebumen Vocational High School (2) to find out how successful student learning is in evaluating using the Quizziz Application in Fiqih Education subjects at MAN 3 Kebumen.This research is a research using qualitative methods. The data collected is in the form of data from interviews, observations and documentation. Data analysis used is data reduction, data presentation and conclusion. The subjects of this study were the Principal of MAN 3 Kebumen, Fiqih Education Teachers at MAN 3 Kebumen, Class XI IPS students.Based on the results of the research, it can be concluded that: (1) the implementation carried out is in accordance with the stages of implementation, namely planning, implementing and evaluating (2) The comparison of the average evaluation scores of students using the Quizizz application with those who don't is very different, namely the average evaluation score using the Quizziz application is 86.4 with a percentage of 86%. Meanwhile, the average evaluation score without using the Quizziz application is 82.5 with a percentage of 82%.